European Union Transregional Cooperation with Latin America: Perspectives, Opportunities, Constraints - Violetta M. Tayar; Evgenii A. Ponomarev (Современная Европа)
The article focuses on modern development of the transregional cooperation between the European Union and Latin America and the Caribbean (LAC). The study is based on official documents, on the European think tanks’ studies, as well as the conceptual vision of the United Nations Economic Commission for Latin America and the Caribbean (ECLAC). The research provides the main directions of short-term and medium-term transregional interaction between the EU and LAC. The authors consider the energy transition as one of the promising areas of transatlantic cooperation for the near future which can stimulate economic growth and production transformations in the LAC region. The article addresses the issue of building the strategic autonomy of the European Union and Latin America and the Caribbean. The authors describe three scenarios of LAC’s development in terms of transregional cooperation with the EU. It is concluded that the European Union in the context of a changing world order is trying to make Latin America and the Caribbean economically and technologically dependent through the implementation of investment programs as part of the green agenda on the way to an accelerated global energy transition.